Preview of Estrogen, Progesterone and an Electrolite Plasma and the Act of Kidney on Sodium, Kalium, and Chorin of Bligon Goatâs Estrous Cycle - Widiyono, I; Putro, P P; Sarmin, Sarmin; Astuti, P; Airin, C M (ANIMAL PRODUCTION, 2013)
Abstract. This research was aimed to obtain status of reproduction hormone and electrolyte plasma and kidneyâs act on electrolyte in normal estrous cycle of 4 healthy female Bligon goats. The electrolyte, hormone and electrolyte clearance study has done in the first day, 3rdâ5th,Â  6thâ16th, and 17thâ18th day of oestrus cycle. Estrogen and progesterone were analyzed with ELISA, while Na, K, Cl were with spectrophotometer. The average difference for each parameter in any period of oestrus cycle was subject to analysis of variance continued by Turkey HSD. The average of estrogen in estrous cycle was 211.25â247.77 pg/dl potential to increase around the estrous and decrease in luteal period (3rdâ5th day and 6thâ16th estrous cycle), and progesterone was 0.21â0.70 ng/dl with significant increase in luteal period (3rdâ5rd day and 6thâ16th estrogen cycle). Na, K, Cl in plasma in estrous cycle were not significantly different. Conclusively, progesterone levels in the late luteal period of Bligon goatâs estrous cycle was significantly higher than that in other periods of oestrus. Estrogen levels tended to increase prior to and during the periods of oestrus and decrease during the luteal period despite the lack of significant changes, also in status of plasma electrolytes and renal acts of electrolytes.Â Key words: Electrolytes, goat, hormone, estrousÂ Abstrak. Penelitian bertujuan untuk mendapatkan status hormon reproduksi dan plasma elektrolit dan reaksi ginjal terhadap elektrolit pada siklus estrus kambing Jawa Randu. Penelitian menggunakan 4 kambing betina sehat yang memiliki siklus estrus normal. Analisa elektrolit, hormon dan bersihan elektrolit dilakukan pada siklus estrus hari pertama, ketiga-kelima, keenam-keenambelas, dan hari ketujuhbelas-kedelapanbelas. Estrogen dan propgesteron dianalisa dengan ELISA, sedangkan Na, K, Cl dianalisa dengan spektofotometer. Rataan perbedaan setiap parameter periode siklus estrus dianalisa dengan analisis ragam dilanjutkan dengan Tukey BNJ. Rataan estrogen dalam siklus estrus adalah 211,25-247,77 pg/dl, dengan potensi peningkatan di sekitar estrogen dan penurunan di fase luteal (siklus estrus hari ke 3-5, dan 6-16), dan rataan progesteron adalah 0,21-0,70 nd/dl dengan peningkatan nyata selama fase luteal (siklus estrus hari ke 3-5, dan 6-16). Na, K, Cl dalam plasma disiklus estrus tidak berbeda nyata. Hasil penelitian menyimpulkan bahwa tingkat progesteron di akhir fase luteal dalam siklus estrus kambing Jawa Randu jauh lebih tinggi dari pada fase lain pada periode estrus. Level estrogen cenderung meningkat sebelum dan selama periode estrus dan menurun selama fase luteal meskipun tidak menunjukkan perubahan nyata, begitu pula pada status elektrolit plasma dan kinerja ginjal terhadap elektrolit.Â Kata kunci: Elektrolit, kambing, hormon, estrus